Relationship between family ownership, agency costs towards financial performance and business strategy as mediation - Enni Savitri (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
This study investigates the relationship between family ownership, agency costs, financial performance, and companies' business strategies. The targeted population of this study were all 143 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2007-2014. About 31% (45) of these manufacturing companies are family companies. The hypotheses were tested using the partial least-square (PLS) method. Our findings reveal that the companies' business strategies are not affected by the family ownership. Family ownership and business strategies influence companies' financial performance. Agency costs influence business strategy and financial performance, and this shows that agency costs contribute to both the increase and decrease of financial performance. Business strategy mediates the relationship between family ownership and financial performance. This shows that family companies do not concentrate on financial goals but rather on the sustainability. Business strategy influences the relationship between agency costs and financial performance. This shows that funds can be redistributed in the course of business strategy planning, which will, in turn, improve the company's development.
Keywords: G32; G34; 650; family ownership; agency costs; financial performance; business strategy